Students' preference on use of in-print and on-screen esl reading materials a case study in odl session among UiTM Kelantan undergraduates / Raja Nur Hidayah Raja Yacob, Anis Idayu Aziz and Amanina Abdul Razak @ Mohamed - Raja Yacob, Raja Nur Hidayah; Aziz, Anis Idayu; Abdul Razak @ Mohamed, Amanina (2021)
This study reports the descriptive statistical findings of a survey of academic reading format preferences used in Open and Distance Learning sessions involving 149 undergraduates from UiTM Kelantan. This study is mainly conducted to examine the preferred format of ESL reading materials among the students, whether they prefer to have their reading materials in-print or on-screen. It is also aimed to investigate the factors that impacted on the preference. The sample was taken from a simple random sampling technique and the data were gathered through a set of questionnaires adapted from the Academic Reading Format International Study (ARFIS) by Mizrachi et al. (2018). The majority of the respondents preferred to read the reading materials in-print over on-screen due to several significant factors including having better focus and retention when reading in-print. This study also showed that the students still prefer to make printed copies of the materials even though they can always read them on-screen